Pengaruh Hubungan Antara Volatilitas Saham, Beta Resiko, dan Return On Investment Dalam Pasar Modal - Maria Yovita R. Pandin; Savira Anjelin; Dyahnesa Harul Puspitaningrum; Mutiara Frakusyari W.; Ivelia Nurma Tis'a Laili (Pusat Riset dan Inovasi Nasional, 2025)
The capital market holds a pivotal role in the economy, serving as a platform where investors assess the balance between risk and return. This study aims to analyze how Stock Volatility influences both Beta Risk and Return on Investment (ROI), as well as to examine the impact of Beta Risk on ROI for stocks listed on the Indonesia Stock Exchange in 2024. Utilizing a quantitative approach through path analysis, the findings indicate that Stock Volatility has a statistically significant negative effect on ROI, while its influence on Beta Risk is not significant. Conversely, Beta Risk shows a significant negative relationship with ROI. These outcomes suggest that higher levels of systematic risk tend to reduce investment returns. The results of this study offer practical insight for investors seeking to understand stock risk behavior in the capital market.